设全集U=Z,集合A={﹣1,1,2},B={﹣1,1},则A∩(CUB)= [ ]
举一反三
- 设全集U={-2,-1,0,1,2},集合A={-1,1,2},B={-1,1},则A∩(∁∪B)为( )
- 设全集U=R,集合A={x|2x-x2>0},集合B={y|y=ex+1},则A∩B( ) A: {x|1≤x<2} B: {x|x>2} C: {x|x>1} D: {x|1<x<2}
- 设全集 U ={-3,-2,-1,0,1,2,3},集合 A ={-1,0,1,2}, B ={-3,0,2,3},则A [img=12x16]17de8834ab412bb.png[/img] CuB =( ) A: {-3,3} B: {0,2} C: {-1,1} D: {-3,-2,-1,1,3}
- 设全集 U ={-3,-2,-1,0,1,2,3},集合 A ={-1,0,1,2}, B ={-3,0,2,3},则A [img=12x16]1803dc74aee45b9.png[/img] CuB =( ) A: {-3,3} B: {0,2} C: {-1,1} D: {-3,-2,-1,1,3}
- 已知集合A={x|-1<x<2},集合B={x|1<x<3},全集U=R